Violência entre (des)iguais: memórias silenciadas nas lutas da Liga Camponesa de Sapé-PB (1962-1964) - Alves, Juliana Ferreira (2019)
This paper intends to contribute to the historiography of peasantry in the state of Paraíba, taking into consideration the Peasant League of Sapé [Liga Camponesa de Sapé] and bringing into discussion the practices of physical and moral violence that were internally present in this organization, based on the memories of peasants who participated in this movement, either as members or as eyewitnesses of this historical event. We also aim to understand the various resistance mechanisms used by the League of Sapé after the assassination of its leader, João Pedro Teixeira, on April 2 of 1962, when it adopted a more inflexible stance in front of the situation of an intensified violence and arbitrariness of the large landowners against the countryman. This new behaviour involved not only the landowners, but also everyone who were against the ideals defended by the peasant organization. Thus, we will make room for the memories of such peasants, so that their reports can break the silence around these facts, enabling us to understand a little more about the history of this movement.